Varieties of Civil Servants Remuneration Policy Reform: A Scenario Planning Analysis - Sugandi, Yogi Suprayogi (UI Scholars Hub, 2018)
This article presents a way of preparing some policy scenario planning in determining the size of the performance index and the price of each position. The performance index is governed by a variety of overlapping central government policies. However, the author is able to provide several scenarios from which one scenario can be selected as a policy option. This way, a variety of ways out of a number of existing scenarios is provided. Options are given to determine the various options to be used in policy decision-making. Contrary to mainstreaming Indonesian practices of remuneration reform that compensates transaction costs of bureaucracy reform policy, there is a sort of facts that those two do not go hand in hand. We pick the City Government of Bandung as a showcase of how this comes to happen, considering its renown as one of reforming local governments. The method used in this study is qualitative method with data collection using Focus Group Discussion (FGD) and secondary data in the form of related regulations and some previous studies. There are six scenarios that can be mapped in the findings, arranged based on the types of available positions. PNS teachers (civil service teachers) as civil servants under the City Government of Bandung in particular are not measured by their own actual performance but, instead, their index of performance is equated one to another in any ranks. This is an example about how performance of civil servants cannot be equated because PNS teachers earn the teacher certification allowance from the central government.